Understanding Children's Power in Bangladesh's Informal Settlements. Issue 3 (2nd September 2021) - Hamilton, Harley; Walters, Vicky; Prinsen, Gerard
Abstract: This article explores power from the perspectives of children living in informal settlements in Dhaka, Bangladesh. It draws on empirical evidence gathered through visual, task-based methods with a small group of children and insights from post-structuralism, development sociology and the anthropology and political economy of Bangladesh to argue that children's power in Dhaka's informal settlements can be understood not as an instrument some agents use to alter the independent action of others, but as a network of boundaries that delimit the field of children's social imagination and possibility. To do this, we introduce children's participation in development studies, showing that the trend has been to exclude children's perspectives. We give an overview of how power has been conceptualized, drawing on insights from post-structuralism and development sociology to present a theoretical framework for how the child participants in this research understood power. Drawing on contextual literature, we then introduce five boundaries of power which constrain and enable agency for children in Dhaka's bastees . The visual, task-based methods we employed with a small group of child participants are introduced. We then discuss five boundaries of power from the perspectives of our research participants: social relationships; financial resources; the natural environment; education and children's work. Drawing links from these findings to existing theories of power, the article concludes by arguing that the operation of power for children in Dhaka's bastees can be understood as a network of boundaries that delimit fields of social imagination and possibility.